COPD-Lower Respiratory Tract Infection Visual Analogue Score (c-LRTI-VAS) validation in stable and exacerbated patients with COPD - Thys van der Molen; Tjip S van der Werf; Hendrik Johannes Prins; Ruud Duijkers; Johannes M A Daniels; Wim Boersma (BMJ Open Respiratory Research)
Background We developed the chronic obstructive pulmonary disease (COPD)-Lower Respiratory Tract Infection-Visual Analogue Score (c-LRTI-VAS) in order to easily quantify symptoms during exacerbations in patients with COPD. This study aimed to validate this score.Methods In our study, patients with stable COPD as well as those with an acute exacerbations of COPD (AECOPD) were included. The results of c-LRTI-VAS were compared with other markers of disease activity (lung function parameters, oxygen saturation and two health related quality of life questionnaires (St Georges Respiratory Questionnaire (SGRQ) and Clinical COPD Questionnaire (CCQ)) and validity, reliability and responsiveness were assessed.Results Eighty-eight patients with clinically stable COPD and 102 patients who had an AECOPD completed the c-LRTI-VAS questionnaire. When testing on two separate occasions for repeatability, no statistically significant difference between total scores was found 0.143 (SD 5.42) (p=0.826). Internal consistency was high across items (Cronbach’s apha 0.755). Correlation with SGRQ and CCQ total scores was moderate to high. After treatment for hospitalised AECOPD, the mean c-LRTI-VAS total score improved 8.14 points (SD 9.13; p≤0.001).Conclusions c-LRTI-VAS showed proper validity, responsiveness to change and moderate to high correlation with other questionnaires. It, therefore, appears a reliable tool for symptom measurement during AECOPD.Trial registration number NCT01232140.